Diallyl disulfide inhibits TNFα induced CCL2 release through MAPK/ERK and NF-Kappa-B signaling. Issue 1 (September 2015) - Bauer, D.; Redmon, N.; Mazzio, E.; Taka, E.; Reuben, J.S.; Day, A.; Sadrud-Din, S.; Flores-Rozas, H.; Soliman, K.F.A.; Darling-Reed, S.
Highlights DADS/TNFα decreased CCL2, Casp8, and Tradd gene expression in a TNBC cell line. DADS/TNFα reduced IKKε protein expression in a TNBC cell line. DADS/TNFα reduced phosphorylated ERK protein expression in a TNBC cell line.